Customer recognition and mobile geo-targeting - Irina Baye; Tim Reiz; Geza Sapi (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2018)
We focus on four important features of mobile targeting. First, consumers' real-time locations are known to sellers. Second, location is not the only factor determining how responsive consumers are to discounts. Other factors such as age, income and occupation play a role, which are imperfectly observable to marketers. Third, sellers may infer consumer responsiveness from their past purchases. Fourth, firms can deliver personalized offers to consumers through mobile devices based on both their real-time locations and previous purchase behavior. We derive conditions that determine how combining behavior-based marketing with mobile geo-targeting influences profits and welfare in a competitive environment. Our setting nests some earlier models of behavior-based price discrimination as special cases and yields additional insights. For instance, different from previous studies we show that pro.t and welfare effects of behavioral targeting may depend on firm discount factor.
Keywords: D43; L13; L15; M37; 330; Mobile Marketing; Location Targeting; Price Discrimination; Customer Data